Endothelin@25 – new agonists, antagonists, inhibitors and emerging research frontiers: IUPHAR Review 12 - Maguire, J J (Br J Pharmacol, 2014)
Since the discovery of endothelin (ET)-1 in 1988, the main components of the signalling pathway have become established, comprising three structurally similar endogenous 21-amino acid peptides, ET-1, ET-2 and ET-3, that activate two GPCRs, ET(A) and ET(B). Our aim in this review is to highlight the recent progress in ET research. The ET-like domain peptide, corresponding to prepro-ET-1(93–166), has been proposed to be co-synthesized and released with ET-1, to modulate the actions of the peptide. ET-1 remains the most potent vasoconstrictor in the human cardiovascular system with a particularly long-lasting action. To date, the major therapeutic strategy to block the unwanted actions of ET in disease, principally in pulmonary arterial hypertension, has been to use antagonists that are selective for the ET(A) receptor (ambrisentan) or that block both receptor subtypes (bosentan). Macitentan represents the next generation of antagonists, being more potent than bosentan, with longer receptor occupancy and it is converted to an active metabolite; properties contributing to greater pharmacodynamic and pharmacokinetic efficacy. A second strategy is now being more widely tested in clinical trials and uses combined inhibitors of ET-converting enzyme and neutral endopeptidase such as SLV306 (daglutril). A third strategy based on activating the ET(B) receptor, has led to the renaissance of the modified peptide agonist IRL1620 as a clinical candidate in delivering anti-tumour drugs and as a pharmacological tool to investigate experimental pathophysiological conditions. Finally, we discuss biased signalling, epigenetic regulation and targeting with monoclonal antibodies as prospective new areas for ET research.